EFL Learners’ Surface Taxonomic Errors of Using Appropriate Verbs in Writing Descriptive Text - Azizah Husda; Fachri Yunanda; Anis Anggraini Siregar (English Teaching and Linguistics Journal (ETLiJ), 2020)
This article dealt with surface taxonomic errors of using appropriate verbs in writing descriptive text. The objectives are to investigate the types of common errors done by EFL learners by describing the dominant errors and also to elaborate on the reason why the learners did the errors in the descriptive text. The subjects of this research consist of 30 Senior High learners from some schools as the representative samples. Descriptive Qualitative Method with a case study design applies to the research. In collecting the data, essay tests and interviews were used. Findings show that there were some types of surface taxonomic errors such as misformation with 110 (60,11%) errors, omissions with 45 (24,59%) errors, addition with 16 (8,74%) errors, and misordering with 12 (6,55%) errors. Thus, misformation is the dominant type found. All of the errors committed to 183 of using appropriate verbs in writing descriptive text. Beyond the dominant errors such as misformation and omission, the errors occurred because some learners put the wrong tenses and verbs. Furthermore, the learners had less comprehension in structures related to the organization of the descriptive text.